ANALISIS PEMBINAAN DALAM PEMINJAMAN DANA BERGULIR PADA UKM DESA DENAI LAMA KABUPATEN DELI SERDANG - Winda Ardiani (Universitas Methodist Indonesia, 2018)
Small and Medium Enterprises (SMEs) are sectors that are proven to be able to contribute greatly in order to overcoming economic problems in Indonesia. Therefore, it is necessary to strengthen the existence of SMEs, one of which is strengthening capital through revolving fund loans. The purpose of this study is to analyze the revolving fund loans undertaken by SMEs. This research is a survey research with a comparison model. The sample in this study was 30 SMEs in the village of Denai Lama, Deli Serdang Municipality, which received revolving funds. There is a change in the coaching category of revolving funds borrowing experienced by respondents both before the coaching arrived at the time after getting coaching. The results showed that there was an increase of 46.03% after the respondents were given training since they had not been given assistance. The revolving fund provider should provide training that is appropriate to the needs of SMEs, then also accompanied by intensive assistance both directly and indirectly so that the use of revolving funds is used properly.